Variability in Step Training Enhances Locomotor Recovery After a Spinal Cord Injury - Shah, Prithvi (2012)
Performance of a motor task is improved by practicing a specific task with added “challenges” to a training regimen. We tested the hypothesis that in the absence of brain control the performance of a motor task is enhanced by training using specific variations of that task. We utilized modifications of step performance training to improve the ability of spinal rats to forward step. After a complete thoracic spinal cord transection, 20 adult rats were divided randomly to bipedally step on a treadmill in the forward, sideward, or backward direction for 28 sessions (20 min, 5d/week) and subsequently tested for their ability to step in the forward direction. Although the animals from all trained groups showed improvement, the rats in the sideward trained and backward trained groups had greater step consistency and coordination along with higher peak amplitudes and total integrated activity of the rectified electromyography signals from selected hindlimb muscles per step during forward stepping than the rats in the forward trained group. Our results demonstrate that by retaining the fundamental features of a motor task (bipedal stepping) the ability to perform that motor task can be enhanced by the addition of specific contextual variations to the task (direction of stepping). Our data suggest that the forward stepping neuronal locomotor networks are partially complemented by synchronous activation of interneuronal/motoneuronal populations that are also a part of the sideward or backward stepping locomotor networks. Accordingly, the overlap and interaction of neuronal elements may play a critical role in positive task transference.